2016
DOI: 10.1155/2016/7494817
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Performance Analysis of the Towers of a Long-Span Bridge Based on GPS Monitoring Technique

Abstract: The present study investigates the parameter identification and the dynamic performance of a long-span bridge tower based on the output of a global positioning system (GPS) health monitoring system. The random decrement (RD) algorithm is used to estimate the tower displacement impulse response. Three methods are applied to extract the dynamic performance including least squares complex exponential (LSCE) method, Hilbert envelope method (HEM), and eigensystem realization algorithm (ERA). Results reveal that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
1
24
0
2
Order By: Relevance
“…Furthermore, the correlation coefficient between the movements of the two directions is −0.01. This result means that the effective movements of the tower occurred in the traffic direction (X-direction), as discussed in [41], and this conclusion confirms that the noise also occurred in this direction. Other previous studies [9,41,42] concluded that the traffic loads are the main loads affecting the bridge.…”
Section: Yonghe Long-span Bridge Evaluationsupporting
confidence: 73%
See 3 more Smart Citations
“…Furthermore, the correlation coefficient between the movements of the two directions is −0.01. This result means that the effective movements of the tower occurred in the traffic direction (X-direction), as discussed in [41], and this conclusion confirms that the noise also occurred in this direction. Other previous studies [9,41,42] concluded that the traffic loads are the main loads affecting the bridge.…”
Section: Yonghe Long-span Bridge Evaluationsupporting
confidence: 73%
“…The output of the two rovers is the RTK time series of global Cartesian coordinates of the installed receivers in the WGS84 coordinate system. Therefore, the collected coordinate data are converted to a local BCS for the analysis of the observations [41]. In this coordinate system, the X-axis represents the traffic direction, and the Y-axis represents the lateral direction of the bridge (Figure 7b).…”
Section: Yonghe Long-span Bridge Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, short-term positions of the measured points [26,37,39]. Data collected based on relative base station is used to measure the accurate position of the monitoring points [15,16,19,21]. Previous GPS monitoring systems are dependent on a wire system to collect data, but nowadays, wireless GPS systems are developed to decrease the monitoring cost [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%